(untitled) (Research, Society and Development, 2020)
This article aims to analyze the theoretical assumptions of P-NPM and governance in its dynamic perspective, as well as the role of external control bodies under this managerial theory that is opposed to the Weberian model. The analysis deals with the changes proposed by the post-new public management, under the direct influence of governance and the need for external control bodies in the Public Administration to dialogue with this new administrative practice. The methodology used was the descriptive as to the object of study, using the hypothetical-deductive approach. The conclusions of the work indicate that the external control bodies have a performance focused on formal aspects, based on sterile legalism, being necessary to reformulate this performance, focusing on the social results obtained, favoring the emergence of new ways of solving problems. and new institutional arrangements.